Teori Hukum dan Filsafat Hukum: Membangun Responsivitas terhadap Perubahan Ekonomi dan Sosial - Makruf, Solihan; Pratama, Brilyan Yudha; Muslimah, Adilla Nur; Pratama, Muhammad Ilham; Shaleh, Chaerul (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2025)
Ideally, legal theory and philosophy of law can shape a legal system that is responsive to economic and social changes. However, in reality, the implementation of law often lags behind the dynamics of change occurring in society. The purpose of this study is to analyze how legal theory and philosophy of law can build responsiveness to economic and social changes, as well as the challenges faced in their implementation. This article falls under library research with a qualitative approach. The method used is normative legal study, analyzing literature, regulations, and relevant documents. The research findings conclude that legal theory ensures that law can adapt to the needs of society and the evolving economy, while philosophy of law provides normative guidance to ensure that law reflects the values of justice, morality, and welfare. Both complement each other in creating regulations that are adaptive to global dynamics while remaining rooted in ethical principles.